Use of non-steroidal anti-inflammatory drugs and adverse outcomes during the COVID-19 pandemic: A systematic review and meta-analysis. (April 2022) - Zhou, Qi; Zhao, Siya; Gan, Lidan; Wang, Zhili; Peng, Shuai; Li, Qinyuan; Liu, Hui; Liu, Xiao; Wang, Zijun; Shi, Qianling; Estill, Janne; Luo, Zhengxiu; et al.
Summary: Background: There are concerns that the use of non-steroidal anti-inflammatory drugs (NSAIDs) may increase the risk of adverse outcomes among patients with coronavirus COVID-19. This study aimed to synthesize the evidence on associations between the use of NSAIDs and adverse outcomes. Methods: A systematic search of WHO COVID-19 Database, Medline, the Cochrane Library, Web of Science, Embase, China Biology Medicine disc, China National Knowledge Infrastructure, and Wanfang Database for all articles published from January 1, 2020, to November 7, 2021, as well as a supplementary search of Google Scholar. We included all comparative studies that enrolled patients who took NSAIDs during the COVID-19 pandemic. Data extraction and quality assessment of methodology of included studies were completed by two reviewers independently. We conducted a meta-analysis on the main adverse outcomes, as well as selected subgroup analyses stratified by the type of NSAID and population (both positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or not). Findings: Forty comparative studies evaluating 4, 867, 795 adult cases were identified. Twenty-eight (70%) of the included studies enrolled patients positive to SARS-CoV-2 tests. The use of NSAIDs did not reduce mortality outcomes among people with COVID-19 (number of studies [N] = 29, odds ratio [OR] = 0.93, 95% confidence interval [CI]: 0.75 to 1.14, I 2  = 89%). Results suggested that the use of NSAIDs was not significantly associated with higher risk of SARS-CoV-2 infection in patients with or without COVID-19 ( N  = 10, OR = 0.96, 95% CI: 0.86 to 1.07, I 2  = 78%; N  = 8, aOR = 1.01, 95% CI: 0.94 to 1.09, I 2  = 26%), or an increased probability of intensive care unit (ICU) admission ( N  = 12, OR = 1.28, 95% CI: 0.94 to 1.75, I 2  = 82% ; N  = 4, aOR = 0.89, 95% CI: 0.65 to 1.22, I 2  = 60%), requiring mechanical ventilation ( N  = 11, OR = 1.11, 95% CI: 0.79 to 1.54, I 2  = 63%; N  = 5, aOR = 0.80, 95% CI: 0.52 to 1.24, I 2  = 66%), or administration of supplemental oxygen ( N  = 5, OR = 0.80, 95% CI: 0.52 to 1.24, I 2  = 63%; N  = 2, aOR = 1.00, 95% CI: 0.89 to 1.12, I 2  = 0%). The subgroup analysis revealed that, compared with patients not using any NSAIDs, the use of ibuprofen ( N  = 5, OR = 1.09, 95% CI: 0.50 to 2.39; N  = 4, aOR = 0.95, 95% CI: 0.78 to 1.16) and COX-2 inhibitor ( N  = 4, OR = 0.62, 95% CI: 0.35 to 1.11; N  = 2, aOR = 0.73, 95% CI: 0.45 to 1.18) were not associated with an increased risk of death. Interpretation: Data suggests that NSAIDs such as ibuprofen, aspirin and COX-2 inhibitor, can be used safely among patients positive to SARS-CoV-2. However, for some of the analyses the number of studies were limited and the quality of evidence was overall low, therefore more research is needed to corroborate these findings. Funding: There was no funding source for this study.